2013
DOI: 10.1103/physrevlett.110.065004
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Localized Energetic-Ion Losses Resulting from Single-Pass Interactions with Alfvén Eigenmodes

Abstract: We report the first observation of prompt neutral beam-ion losses due to nonresonant scattering induced by toroidal and reversed shear Alfvén eigenmodes in the DIII-D tokamak. The coherent losses are of full energy beam ions expelled from the plasma on their first poloidal orbit. The first-orbit loss mechanism causes enhanced, concentrated losses on the first wall exceeding nominal levels of prompt losses. The loss amplitude scales linearly with the mode amplitude. The data provide a novel and direct measure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 21 publications
3
33
0
Order By: Relevance
“…An example (first reported in Ref. 21) is shown in Fig. 4, during the early plasma current ramping phase in a neutral beam heated reversed magnetic shear plasma, two tangential co-current neutral beams are alternatively injected.…”
Section: B Radial Displacement Of Fast Ions Due To Individual Alfvénmentioning
confidence: 99%
“…An example (first reported in Ref. 21) is shown in Fig. 4, during the early plasma current ramping phase in a neutral beam heated reversed magnetic shear plasma, two tangential co-current neutral beams are alternatively injected.…”
Section: B Radial Displacement Of Fast Ions Due To Individual Alfvénmentioning
confidence: 99%
“…The "local resonance" is also called "single-pass resonance" for particles which are lost after interacting with the AE mode in a single bounce orbit in some papers. 5,11 The calculated radial displacement (about a few centimeters) after one bounce is proportional to the AE amplitude with the same frequency. The local resonance condition is given by…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9] The losses were measured using a Fast Ion Loss Detector (FILD) with a high frequency response and were coherent with the Alfv en eigenmodes. It was shown that the coherent losses in DIII-D mainly come from trapped particles whose orbits are close to the tokamak wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a loss detector, the signal from this toroidally localized source is often much larger than axisymmetric losses [7]. Since the beam deposition and equilibrium fast-ion orbits are well understood, these ions can be used to measure the effect of waves that deflect the orbits [7,8].…”
Section: Introductionmentioning
confidence: 99%